Clinical observation and histopathological evaluation of pulp after pulpotomy of primary teeth with formocresol and biodentine: Pulpotomy of primary teeth with formocresol and biodentine - Guang, Jianxia; Li, Junke; Hao, Lele (Cellular and Molecular Biology, 2022)
Pulpotomy is the typical treatment for keeping deciduous teeth until exfoliation. Formocresol is one of the most common materials used in dental pulpotomy. Due to the side effects of this drug, its replacement with other substances seems necessary. Therefore, this study compared clinical and histopathological evaluations of primary pulpotomy molars with formocresol and biodentine. In this clinical trial, 66 second-mandibular deciduous molars of children aged 6 to 9 years who met the criteria for pulpotomy were selected. Pulpotomy of the teeth was performed using formocresol and biodentine. For each patient, one tooth was randomly placed in the pulpotomy group with formocresol. The other tooth was placed in the pulpotomy group with biodentine. Then the crowns of the teeth were restored with stainless steel veneer. We recorded clinical and radiographic results of these teeth over six months and one year. The teeth were then extracted after 12 months, and hematoxylin-eosin staining was performed for histopathological evaluations. The obtained data were analyzed by Fisher test and SPSS software version 22. The results showed that clinical success of 6 and 12 months of pulpotomy in both groups was 100%. The 6-month radiographic evaluation of the formocresol group was 84.8%, and the biodentine group was 93.9% (p = 0.21). The success of 12-month radiographs of the formocresol group and the biodentine group were 81.8 and 93.9, respectively (p = 0.13). Also, the histopathological evaluation showed that in the biodentine group, there was mild inflammation in two teeth, two teeth showed moderate inflammation, and two teeth showed severe inflammation. In the formocresol group, severe inflammation was seen in two cases. Mild inflammation was not seen in any of the teeth. Moderate inflammation was seen in one tooth. It was found that there was no significant difference between the two groups in terms of inflammation (P >0.05). No necrosis was seen in any of the biodentine group teeth, and there was necrosis in four teeth of the formocresol group. There was a significant difference between the two groups regarding necrosis (P = 0.032). There was no significant difference between the two groups regarding abscess (P> 0.05). According to the obtained results, biodentine could be a suitable alternative for mandibular second molar pulpotomy.